China–US trade War: an Indonesian perspective. Issue 2 (4th May 2019) - Pangestu, Mari
ABSTRACT: This paper takes a holistic approach to the effect of US-China trade war on Indonesia. The paper starts by laying out the context of the rise of protectionism and nationalism, comparing developed and developing country context, and its various causes such as unequal distribution of benefits and responses to the rise of China. The new US approach focusing on goods trade deficit, targeting mainly China but also other countries, including Indonesia and it should be seen as a tool to address the real concerns of the US regarding unfair trade, such as technology transfer, industrial subsidies and trade and investment distortions. It also reflects the US view of the inadequacy of the WTO. In terms of direct impact, the US-China trade war is creating uncertainities to global growth and in particular any decline in China's growth is likely to hit Indonesia and other ASEAN countries given that China has become their number one trading partner. As for benefit from trade diversion and investment relocation to avoid the trade war, given the structure of its exports and lack of integration in the Global Value Chains, Indonesia is unlikely to benefit compared to several other Southeast Asian countries, such as Vietnam. However, any net benefit from this, will far outweigh the cost of the uncertainty in the rules based multilateral trading system (MTS) and the retreat of the US leadership to safeguard the MTS. The paper looks at how the current US unilateralism is framed in a carrot and stick approach, which does not benefit developing countries like Indonesia. To fill the leadership vacuum to maintain an open rules based order, other countries need to take the leadership position. This can be done by pursuing their own unilateral agenda of structural reforms, increasing regional economic integration and take collective leadership to conduct necessary reforms of the WTO especially on issues that are at the heart of the US-China trade war such as industrial subsidies, strengthening IPR, investment issues related to technology transfer, and competition policy and the level playing field.